2010
DOI: 10.1038/aps.2010.150
|View full text |Cite
|
Sign up to set email alerts
|

ZSTK474, a novel phosphatidylinositol 3-kinase inhibitor identified using the JFCR39 drug discovery system

Abstract: JFCR39 is an informatic anticancer drug discovery system that utilizes a panel of 39 human cancer cells coupled with a drug-activity database. This system not only provides disease-oriented information but can also predict the mechanism of action of a given antitumor agent. Development of a phosphatidylinositol 3-kinase (PI3K) inhibitor as an anticancer drug candidate has attracted a great deal of attention from both academia and industry because PI3K is known to be closely involved in carcinogenesis. ZSTK474 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 74 publications
1
52
0
Order By: Relevance
“…In summary, inhibiting the PI3K-AktmTOR pathway can prevent TM-induced ER stress. There was no significant difference in inhibition caused by rapamycin and NVP-BEZ235 treatment, This result might have been due to the competitive inhibition effect of NVP-BEZ235, an observation consistent with that of Kong and Yamori (2010) who reported that NVP-BEZ235 and ATP were competitive inhibitors of mTOR and PI3K, but caused more reactive inhibition of mTOR. but the inhibition resulting from the treatment with LY294002 was significantly different.…”
Section: Discussionsupporting
confidence: 85%
“…In summary, inhibiting the PI3K-AktmTOR pathway can prevent TM-induced ER stress. There was no significant difference in inhibition caused by rapamycin and NVP-BEZ235 treatment, This result might have been due to the competitive inhibition effect of NVP-BEZ235, an observation consistent with that of Kong and Yamori (2010) who reported that NVP-BEZ235 and ATP were competitive inhibitors of mTOR and PI3K, but caused more reactive inhibition of mTOR. but the inhibition resulting from the treatment with LY294002 was significantly different.…”
Section: Discussionsupporting
confidence: 85%
“…With multiple efforts under way in academia and industry to develop clinically relevant inhibitors against PI3K, a number of inhibitors have entered clinical trials, including PI3K selective inhibitors (either isoform-specific or pan-class I PI3K inhibitors) and dual PI3K/mTOR inhibitors (Pal and Mandal, 2012). Among them, dual PI3K/mTOR inhibitors target both PI3K and mTOR and avoid reactivation of PI3K induced by mTOR inhibition (Li et al, 2010), pan-PI3K inhibitors target all isoforms of class I PI3Ka (Kong and Yamori, 2010), and isoform-specific PI3K inhibitors preferentially target one isoform of class I (Engelman, 2009). Although most drug candidates now in clinical trials are pan-PI3K inhibitors or dual PI3K/mTOR inhibitors, generation of more selective agents is supposed to be advantageous to reduce side effects.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K has been validated as a therapeutic tumor target of increasing interest from the research community of tumor biology and cancer therapeutics as well [8,9] . Due to efforts in academia and industry to develop clinically relevant inhibitors, a number of pan-or isoform-specific PI3K inhibitors have been identified and developed as potential molecularly targeted anticancer therapies, including GDC0941 (pan-PI3K), A66 (PI3Kα), TGX221 (PI3Kβ), AS604850 (PI3Kγ), and CAL-101 (PI3Kδ) [6,[10][11][12][13][14] . Isoform inhibitors may enhance targeting and reduce toxicity, whereas pan-PI3K inhibitors are thought to be more potent with wide antitumor spectrum.…”
Section: Introductionmentioning
confidence: 99%